The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s0248-4900(01)01178-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of peroxisome proliferator‐activated receptors alpha and gamma in differentiating human colon carcinoma Caco‐2 cells

Abstract: The expression of peroxisome proliferator-activated receptors alpha (PPARalpha) and gamma (PPARgamma) was studied in the human adenocarcinoma Caco-2 cells induced to differentiate by long term culture (15 days). The differentiation of Caco-2 cells was attested by increases in the activities of sucrase-isomaltase and alkaline phosphatase (two brush border enzymes), fatty acyl-CoA oxidase (AOX) and catalase (two peroxisomal enzymes), by an elevation in the protein levels of villin (a brush border molecular marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 68 publications
1
16
1
2
Order By: Relevance
“…HT-29 and HCT116 cells remained undifferentiated in the same culture delay. As previously shown (26), catalase content used as a marker of differentiation was increased during spontaneous differentiation process occurring in Caco-2 cells, but also in HT-29 MTX 10 -5 M Rev cells. We demonstrated that PPARÁ protein was present in these cells with an estimated Mr at 50 kDa (Fig.…”
Section: Presence Of Ppará Protein In Colon Derivedsupporting
confidence: 72%
“…HT-29 and HCT116 cells remained undifferentiated in the same culture delay. As previously shown (26), catalase content used as a marker of differentiation was increased during spontaneous differentiation process occurring in Caco-2 cells, but also in HT-29 MTX 10 -5 M Rev cells. We demonstrated that PPARÁ protein was present in these cells with an estimated Mr at 50 kDa (Fig.…”
Section: Presence Of Ppará Protein In Colon Derivedsupporting
confidence: 72%
“…The importance of PPARg in the colon is implied by variation of expression of PPARg within the distal and proximal colon (1,2) as well as by increased levels in more differentiated epithelial cells (1,(3)(4)(5)(6). Free fatty acids are known to bind to PPARg with polyunsaturated fatty acids having the higher binding affinity than saturated or monounsaturated fatty acids (7,8) and with greater activation stemming from oxidized polyunsaturated fatty acids than unoxidized fatty acids (9).…”
Section: Introductionmentioning
confidence: 99%
“…Among PPARs, PPARg is primarily expressed in adipose tissue and is an important regulator of adipocyte differentiation (Lowell, 1999). Recent studies have demonstrated the presence of PPARg in colon, prostate, bladder, breast, and other human cancer cells (Elstner et al, 1998;Kubota et al, 1998;Mueller et al, 1998;Sarraf et al, 1998;Chang and Szabo, 2000;Huin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%